Glutathione S-transferase polymorphisms may be associated with risk of oedematous severe childhood malnutrition. - Marshall, K; Howell, S; Reid, M; Badaloo, A; Farrall, M; Forrester, T; McKenzie, C (2006)
It has been estimated that more than 50 % of deaths before the age of 5 years have undernutrition as an underlying cause. Severe childhood malnutrition, an extreme form of undernutrition, occurs as oedematous and non-oedematous syndromes. The reasons why only some children develop oedematous severe childhood malnutrition (OSCM) have remained elusive, but the heterogeneity of clinical appearances among children from relatively homogeneous backgrounds suggests that interindividual variation in susceptibility to OSCM may exist. We investigated variants of four glutathione S-transferase (GST) genes in a retrospective study among subjects (n 136) previously admitted to the Tropical Metabolism Research Unit, Jamaica, for the treatment of either OSCM (cases) or non-oedematous severe childhood malnutrition (controls). We found that GSTP1 Val(105) homozygotes were significantly more common among the cases (odds ratio (OR) 3.5; 95 % CI 1.1, 10.8). We also found an association of borderline significance between non-deletion GSTT1 genotypes (i.e. +/+ or +/0) and OSCM (OR 2.4; 95 % CI 1.0, 5.9). There was no significant association between OSCM and any of the other GST variants. These preliminary findings suggest that genetic variation within the GST superfamily may contribute to the risk of OSCM. Additional, larger data sets and studies of variants in other candidate genes are required in order to properly assess the true contribution, if any, of genetic variation to risk of OSCM. Such studies may improve our understanding of the causes of clinical heterogeneity in malnutrition.